Spectrophotometric determination of iron (III) catalyst in organic compound chlorinations - Rigas, Fotis; Doulia, Danae (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
In the science or industrial practice of chemical processes, iron (III) is sometimes used as a catalyst in organic compound chlorinations due to its effectiveness and low cost. Thus, a fast and easy method of determination in the system is useful especially when metallic iron is used as a precursor which is readily converted into iron (III) chloride by the gaseous chlorine used in the chlorination reactor. In the latter case, the determination of the produced catalytically effective iron (III) is a prerequisite for controlling the kinetic progress of chlorination. In this work, a method for the spectrophotometric determination of iron (III) chloride in organic media after complexation with methyl ethyl ketone is investigated. The formation of a strong o-complex of iron (III) with methyl ethyl ketone allows direct determination of iron at 360 nm. Beer’s law is valid up to absorbance 2.42, where the iron (III) concentration is 20.7 mg·L-1, with molar absorptivity (e) equal to 6.532×103 L·mol-1·cm-1 and Sandell’s sensitivity 8.5×10-3 ug·cm- 2. Standing time for color development is of the order of a few seconds and stability of color measurements exceeds 12 months. The method may be used among other applications in organic compounds chlorinations catalyzed by iron. These systems are complicated due to the coexistence of various complexes. Nevertheless, the method proposed being simple, fast, and not depending on the composition of the chlorination mixture and the amount of methyl ethyl ketone added was found to be suitable.